The Effect of Project Based Learning Model on Mathematical Problem Solving Ability of Algebraic Operation Material in Class VII SMP Negeri 3 Pematang Siantar - Hutabarat, Romla Eka Monalisa; Sidabutar, Ropinus (EduMatika: Jurnal MIPA, 2023)
This study aims to determine how the effect of using the Project Based Learning (PjBL) learning model on students' mathematical problem solving skills in class VII SMP Negeri 3 Pematang Siantar. The research method used in this study is an experimental method with a research design of Nonequivalent Control Group Design. The population in this study were all seventh grade students of SMP Negeri 3 Pematang Siantar in the 2023/2024 academic year. Sampling was carried out using purposive sampling technique, so the sample obtained was class VII-7 students totaling 30 people as a control class and class VII-10 students totaling 30 people as an experimental class. The instrument used in this study was a problem solving ability test in the form of descriptions. Based on the data analysis, it can be concluded that there is an effect of the Project Based Learning learning model on students' mathematical problem solving skills. The results of data analysis obtained the average value of the class using the Project Based Learning (PjBL) learning model of 82.87 and the average class with a conventional model of 67.50. The results of hypothesis testing obtained t_hitung = 5.507 and t_table = 2.002. If t_count is greater than t_table, the hypothesis H_(0) is rejected. Based on the previous explanation, it can be concluded that the use of Project-based learning (PjBL) learning model has an influence on students' mathematical problem solving ability on algebraic material in class VII SMP Negeri 3 Pematang Siantar.